021 Determinants of natalizumab-associated PML outcomes. Issue 6 (27th May 2022) - Kappos, Ludwig; McGuigan, Chris; Derfuss, Tobias; Giovannoni, Gavin; Oh, Jiwon; Ren, Zheng; McCarthy, Kerry; Chang, Ih; Campbell, Nolan
Abstract : Introduction: Natalizumab treatment is associated with risk of progressive multifocal leukoencephalopa- thy (PML). Following PML diagnosis, plasma exchange (PLEX) may be used to enable rapid natalizumab clearance. This analysis explores the impact of PLEX and patient characteristics on natalizumab-associated PML outcomes. Methods: Patients with multiple sclerosis, natalizumab-associated PML, and PLEX treatment status as of September 2018 were included (PLEX+, n=616; PLEX−, n=109). The primary outcome was 2-year survival after PML diagnosis. Kaplan-Meier estimates of cumulative survival for patients with/without PLEX were stratified by log JC virus (JCV) viral copy number (VCN) at PML diagnosis. Hazard ratios for survival were based on a Cox proportional hazards model. Results: The cumulative probability of 2-year survival for PLEX+ vs PLEX− patients was 88.2% vs. 89.3% (P=0.857) with log VCN ≤5, 73.8% vs. 89.3% (P=0.097) with log VCN >5 to ≤7, and 68.2% vs. 78.9% (P=0.435) with log VCN >7. Improved survival was associated with younger age, asymptomatic presentation, localized PML lesions, and lower log JCV VCN. Conclusions: PLEX had no significant effect on survival rates. Numerically worse 2-year survival probabilities were observed with PLEX regardless of PML presentation, suggesting PLEX is not effective for improving post-PML outcomes. Support: Biogen. Disclosures: Included on the poster. g.giovannoni@qmul.ac.uk